2017
DOI: 10.1536/ihj.16-415
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification of Future Left Ventricular Dysfunction for Patients with Indications for Right Ventricular Pacing due to Bradycardia

Abstract: SummaryAlthough right ventricular (RV) pacing is the only effective treatment for patients with symptomatic bradycardia, it creates left ventricular (LV) dyssynchrony, which can induce LV dysfunction and heart failure. The current criterion for consideration of cardiac resynchronization therapy (CRT) is LV ejection fraction (LVEF) ! 35%, but indication for CRT in patients required for RV pacing with LVEF > 35% remains unclear.We studied 40 patients, all LVEF "35%, who had undergone implantable cardioverter-def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…Fourth, LVEF was measured under right ventricular pacing at CS diagnosis and after corticosteroid therapy in most cases, which might cause underestimation. 26) Further studies with a larger population including patients without CAVB are required to support the present results. Conclusion: In patients of CS with CAVB without history of extracardiac sarcoidosis, the diagnosis of CS may be delayed.…”
Section: Role Of Echocardiography For Early Diagnosis Of Csmentioning
confidence: 59%
“…Fourth, LVEF was measured under right ventricular pacing at CS diagnosis and after corticosteroid therapy in most cases, which might cause underestimation. 26) Further studies with a larger population including patients without CAVB are required to support the present results. Conclusion: In patients of CS with CAVB without history of extracardiac sarcoidosis, the diagnosis of CS may be delayed.…”
Section: Role Of Echocardiography For Early Diagnosis Of Csmentioning
confidence: 59%
“…In this study, we showed that age, renal dysfunction, decreased LVEF, and appropriate ICD shocks were significant predictors of death in the univariate analysis, similar to that reported in previous studies. [24][25][26] We showed in a multivariate analysis that high BNP level, sedentary status but awake at the time of occurrence of an inappropriate therapy, and cause of inappropriate therapy were novel and potent predictors of increased mortality. A unique aspect of the current study was the measurement of BNP.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac pacing is an effective treatment for patients with bradyarrhythmia, but pacing-induced cardiomyopathy after right ventricular pacing continues to be reported in the literature, especially in pacing-dependent patients with Chen, ET AL decreased cardiac functions. [11][12][13][14] In recent years, selective site pacing from the right ventricular mid-septum has made rapid progress, and some studies suggest that it results in better cardiac function and prognosis than the right ventricular apical pacing. 15,16) However, based on the existing information from evidence-based medicine, right ventricular septal pacing did not show significant advantages.…”
Section: Discussionmentioning
confidence: 99%